Platelet-Rich Plasma Injections in Chronic Lateral Ankle Instability: A Case Series - Medina-Porqueres, Iván; Martin-Garcia, Pablo; Sanz-De-Diego, Sofia; Reyes-Eldblom, Marcelo; Moya-Torrecilla, Francisco; Mondrago-Cortes, Rafael; Rosado-Velazquez, Daniel; Gómez-Cáceres, Abel (MDPI, 2024)
The platelet-rich plasma (PRP) approach may be an effective treatment for joint and cartilage pathologies. However, the rationale for its effectiveness on joint instability is limited. This study aimed to assess the safety and effectiveness of PRP injections in patients with chronic lateral ankle instability (CLAI). This retrospective study was performed at a single-center outpatient clinic between January 2015 and February 2023 and included pre-intervention assessment and short-term follow-up. Patients were excluded if they had received previous surgical treatment or had constitutional hyperlaxity, systemic diseases, or grade II or III osteoarthritis. The clinical and functional evaluation consisted of the Karlsson score, the Cumberland Ankle Instability Tool (CAIT), Good’s grading system, the patient’s subjective satisfaction level, and the time required to return to exercise. The entire PRP therapy regime consisted of three PRP administrations at 7-day intervals and follow-up appointments. PRP was administered both intraarticularly and into talofibular ligaments. A total of 47 consecutive patients with CLAI were included, 11 were female (23.4%), with a mean age at intervention of 31.19 ± 9.74 years. A statistically significant improvement was found in the CAIT and Karlsson scores at 3 months (27.74 ± 1.68 and 96.45 ± 4.28, respectively) relative to the pre-intervention status (10.26 ± 4.33 and 42.26 ± 14.9, respectively, p < 0.000). The mean follow-up of patients with CLAI was 17.94 ± 3.25 weeks. This study represents successful short-term functional and clinical outcomes in patients with CLAI after PRP treatment, with no adverse effects. It demonstrates the feasibility of a randomized controlled trial to further assess this therapy.
Keywords: Cartílagos; Articulaciones; platelet-rich plasma; Growth factors; Injection; Ankle instability; Recurrent ankle sprain; Lateral ligament injury; Chronic injury